2008
DOI: 10.1002/bdd.605
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin pharmacokinetics in humans

Abstract: The purpose of this study was to examine the pharmacokinetics of quercetin aglycone as well as its conjugated metabolites and to develop a population pharmacokinetic model for quercetin that incorporates enterohepatic recirculation. The stability of quercetin in different matrices at various temperatures and pH, and the quercetin content of six capsules of the herbal preparation Quercetin-500 Plus were determined by HPLC. Subjects received quercetin 500 mg three times daily and blood and urine samples were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(157 citation statements)
references
References 34 publications
8
146
1
2
Order By: Relevance
“…Moreover, in the case of repeated ingestion of polyphenol-rich foods, the exposure of PMNs to these compounds would last much longer in vivo than in our experiments, which indubitably augments their effects. This situation can be of particular importance in the case of quercetin, which undergoes enterohepatic circulation (Moon et al, 2008) with a plasma half-life that extends from 11 to 28 h (Manach et al, 2005). Even supposing that this compound undergoes glucuronidation in the liver, it can influence PMNs in this form (Suri et al, 2008); furthermore, these cells have beta glucuronidase activity, which may deconjugate quercetin (Shimoi & Nakayama, 2005).…”
Section: Relevance Of In Vitro Results To In Vivo Conditionsmentioning
confidence: 99%
“…Moreover, in the case of repeated ingestion of polyphenol-rich foods, the exposure of PMNs to these compounds would last much longer in vivo than in our experiments, which indubitably augments their effects. This situation can be of particular importance in the case of quercetin, which undergoes enterohepatic circulation (Moon et al, 2008) with a plasma half-life that extends from 11 to 28 h (Manach et al, 2005). Even supposing that this compound undergoes glucuronidation in the liver, it can influence PMNs in this form (Suri et al, 2008); furthermore, these cells have beta glucuronidase activity, which may deconjugate quercetin (Shimoi & Nakayama, 2005).…”
Section: Relevance Of In Vitro Results To In Vivo Conditionsmentioning
confidence: 99%
“…Mizuma (2009) reported that extensive intestinal glucuronidation of raloxifene accounts for its low oral bioavailability. Quercetin likewise has low oral bioavailability (Moon et al, 2008), which may arise from its extensive intestinal glucuronidation. Wang et al (2006) found that rat intestinal microsomal CL int , V max , and K m values for glucuronidation of the isoflavones were unrelated to rates of glucuronidation in an intestinal perfusion model.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary or supplemental quercetin has low oral bioavailability and is extensively glucuronidated, sulfated, and methylated in intestine and liver with large interindividual variations (Mullen et al, 2006;Moon et al, 2008). These phase II enzyme conjugations facilitate quercetin efflux back to the intestinal lumen before its systematic distribution and play a role in its limited bioavailability (van der Woude et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A pharmacokinetic study showed that the maximum plasma concentration (C max ) of quercetin aglycone was 15.4 ng/mL (equivalent to 51 nM) following oral intake of 500 mg quercetin [52]. Taking into account the relatively low content of quercetin in cranberry supplements (about 50 µg in a 500 mg capsule), in vivo concentrations of quercetin from cranberry are not expected to be close to the reported IC 50 values [44,45].…”
Section: Cranberrymentioning
confidence: 94%
“…MPA is an immunosuppressive drug that is metabolized in the liver by UGT1A9 and in the intestine by UGT1A7, 1A8, 1A9, and 1A10 [70][71][72]. In HLM, IC 50 values for inhibition by quercetin and kaempferol were 19.1 and 23 µM which are many fold higher than the expected plasma C max of flavonoids [52]. Therefore, inhibition of systemic MPA metabolism in vivo is unlikely.…”
Section: Ginkgomentioning
confidence: 99%